85.5k views
3 votes
1) y = 2x – 17
-3x – y=-13

User Ajaristi
by
5.8k points

1 Answer

2 votes

Answer:

x = 6, y = -5 → (6, -5)

Explanation:


\left\{\begin{array}{ccc}y=2x-17&\text{subtract}\ 2x\ \text{from both sides}\\-3x-y=-13\end{array}\right\\\\\underline{+\left\{\begin{array}{ccc}-2x+y=-17\\-3x-y=-13\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad-5x=-30\qquad\text{divide both sides by (-5)}\\.\qquad\boxed{x=6}\\\\\\\text{Substitute the value of x to the first equation}\\\\y=2(6)-17\\y=12-17\\\boxed{y=-5}

User Michael Simons
by
6.4k points